Предмет: Алгебра,
автор: MrHolmes44
Упростите выражение:
1)
2)
Ответы
Автор ответа:
0
1
x-x/(x-1)=(x²+x-x)/(x+1)=x²/(x-1)
2
(m+2)/4m-1/(m+4)=(m²+4m+2m+8-4m)/[4m(m+4)]=((m²+2m+8)/[4m(m+4)]
x-x/(x-1)=(x²+x-x)/(x+1)=x²/(x-1)
2
(m+2)/4m-1/(m+4)=(m²+4m+2m+8-4m)/[4m(m+4)]=((m²+2m+8)/[4m(m+4)]
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Биология,
автор: Nastya23092007
Предмет: Русский язык,
автор: gorkovenkoviktoria24
Предмет: Математика,
автор: 497гонка
Предмет: Алгебра,
автор: patimatmamaeva